Kulturell komplexitet och komplexa kulturer - Ronström, Owe (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1994)
One of the odd things about cultural studies is that "culture" is both the most important object of its pursuit and the central theoretical concept used to achieve that objective. For that very reason it is necessary to constantly call the implications of the concept of culture into question. Previously, the existence of clearly defineable units — "culture" — has been taken for granted. Concurrent with the interest cultural researchers have begun to display for big-city life, modern, hi-tech societies and the like, awareness has increased about the fact that a new arsenal of concepts is necessary in order to better treat cultural complexity. In his book Cultural Complexity, social anthropologist Ulf Hannerz discusses a number of concepts and tools which take their impetus from the apprehension of culture as a process. Hannerz considers culture as having two loci: the external forms through which meaning can be make accessible to all, and the cognitive prerequisites in the minds of individuals which enable them to interpret these forms meaningfully. He sees culture as the flow between these external forms and the internal mental structures. The problem discussed here is that this cultural flow does not spread itself evenly over a population. Thus Hannerz concludes that cultural analysis of complex modern societies must keep in mind the relationship between three dimensions of culture: ideas and ways of thinking; the forms through which meaning can be externalized and made accessible to others; and social distribution, ie. how and to what extent these ideas and forms are disseminated among the population.